THE USE OF LINEAR BODY MEASUREMENTS PREDICTORS OF BODY WEIGHT OF DONKEYS AT BLOUBERG LOCAL MUNICIPALITY, LIMPOPO, SOUTH AFRICA - Thobela Louis Tyasi (Mesopotamia Journal of Agriculture)
The current study was conducted to estimate body weight (BW) by using body measurements including thoracic circumference (TC), withers height (WH), body length (BL), rump height (RH) and front leg length (FLL) of donkeys. The study was conducted at three villages (Thorne, Archibalt, and Genau) of Blouberg Local Municipality, Limpopo, South Africa. A total of 74 donkeys (40 males and 34 females) aged from 3 to 4 years were used in the current study. Data were analyzed using Pearson correlation and simple linear regression. Correlation results indicated that in female donkeys, BW had positive and highly statistical significant (p  0.01) correlation with WH (r = 0.67) and not significant correlated (p  0.05) with TC (r = 0.14) and FLL (r = 0.28). In male donkeys, BW had positive and highly statistical significant (p  0.01) correlation with RH (r = 0.60) and not significant correlated (p  0.05) to FLL (r = 0.27). Regression findings indicated that WH had the highest R2 = 0.45 in female donkeys, while RH had the highest R2 = 0.36 in male donkeys.